Abortion as an Essential Health Service in Latin America During the COVID-19 Pandemic - Ramón Michel, Agustina; Ariza Navarrete, Sonia; Chávez, Susana (Frontiers in Global Women's Health, 2022)
Background The rapid increase in demand for health services as a result of the COVID-19 outbreak has created significant challenges for health systems. National and international health authorities have declared reproductive health services as essential, particularly those related to prevention, care during pregnancy, delivery and postpartum, as well as abortion services. This research was conducted by a regional team in cooperation with nine local organizations that are members of the Latin American Consortium against Unsafe Abortion (Consorcio Latinoamericano Contra el Aborto Inseguro, CLACAI). Objectives Our research aimed to examine the provision of reproductive healthcare services, with a focus on abortion, in nine countries during the first few months of the pandemic (March to September 2020). Methods Our research design developed a set of quantitative and qualitative indicators to monitor the availability and accessibility of abortion services during the COVID-19 pandemic. Researchers collected the quantitative data by reviewing regulations and other documents, government and civil society reports, and official statistics; the qualitative data was acquired through interviews with key actors, and non-representative surveys completed by healthcare professional and end users of reproductive services. Results Although six of the nine countries we researched deemed reproductive health services essential, only two of these six countries considered abortion services to be essential, and all nine countries reported difficulties in accessing abortion services. Restrictive abortion laws remained in place in the majority of countries (seven), and as a result access to abortion services became even more limited than it had been before the pandemic. At the same time, good practices to facilitate access to abortion services in healthcare facilities, updated regulatory frameworks, and collaboration between civil society and government agencies were identified and should continue to be promoted even after the pandemic crisis has subsided. Conclusions The pandemic catalyzed what was already happening in each country, and as such abortion services have become more accessible in countries like Argentina, where the so-called green wave has been generating social, legal and policy changes, whereas in countries such as Ecuador, where abortion is legally restricted and opposed to by the government, access to safe abortion became even more difficult than it was before the pandemic. However, the general trend has been a lack of adequate adaptation in order to guarantee quality in abortion care. That said, there have also been some interesting and positive service provision initiatives, such as telemedicine, implemented in at least two countries, which, if maintained long-term, could improve access to safe abortion.